2015
DOI: 10.1021/acs.jnatprod.5b00255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physicochemical Properties for Drugs of Natural Origin

Abstract: The impact of time, therapy area, and route of administration on 13 physicochemical properties calculated for 664 drugs developed from a natural prototype was investigated. The mean values for the majority of properties sampled over five periods from pre-1900 to 2013 were found to change in a statistically significant manner. In contrast, lipophilicity and aromatic ring count remained relatively constant, suggesting that these parameters are the most important for successful prosecution of a natural product dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…These physicochemical properties are comparable to the commercial antifungals and antimicrobial peptides analyzed here. Furthermore, the molecular weight, logD 7.4 , and polar surface area are in line with a large number of natural products used to treat infections, 37 indicating that AEC5 may serve as a good lead for antifungal therapeutic development. Furthermore, the stability of AEC5 in human serum was determined following well established protocols.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 79%
“…These physicochemical properties are comparable to the commercial antifungals and antimicrobial peptides analyzed here. Furthermore, the molecular weight, logD 7.4 , and polar surface area are in line with a large number of natural products used to treat infections, 37 indicating that AEC5 may serve as a good lead for antifungal therapeutic development. Furthermore, the stability of AEC5 in human serum was determined following well established protocols.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 79%
“…For example, Lipinski's "Rule of Five" for drug-like molecules can be employed to bias library members towards orally bioavailable leads and/or drugs, while other property combinations can be pursued to facilitate the development of injectables. 7 Indeed, a statistical analysis of drugs derived from a natural progenitor showed that physicochemical properties can vary markedly across different therapy areas. 7 Computational design using physicochemical properties prior to derivative synthesis has been increasingly used to produce more desirable libraries.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of lipophilic aliphatic chains at C-6 generally led to an increase in activity, while arylation at C-13 resulted in decreased potency. The most potent analogue, 3, bore a lauroyl group (IC 50 2.91-6.78 µM), which was more active than the NP scaffold 1 (IC 50 Oleanolic acid (6) and maslinic acid (7) are found in high concentrations in olive-pomace oil and can be obtained in large amounts from the solid waste resulting from olive-oil production. 21 Triterpenoids such as 6 and 7 possess a range of medicinal benefits including anti-inflammatory, hepatoprotective, analgesic, anti-microbial, virostatic, anticancer, and anti-HIV activities.…”
Section: Examples Of Analogue Libraries Based On Isolated Np Scaffoldsmentioning
confidence: 99%
“…This is because each representation has its own advantages and disadvantages: molecular scaffolds are straightforward to interpret but they capture part of the chemical structure, missing the information given by side chains [7]; structural fingerprints usually capture the information of the entire structure but are harder to interpret [8]. Whole molecular properties such as physicochemical properties are easy to interpret and are the basis of several drug- and lead-like empirical rules [9, 10]. However, these properties do not always distinguish the collections e.g., it is not uncommon for different compounds to share very similar property profiles.…”
Section: Introductionmentioning
confidence: 99%